Synthesis and characterization of BNKT/ZnO ferroelectric lead-free nanocomposites - C. Wichasilp (2018)
In this research, the effects of ZnO nanoparticles additive on crystallization behavior, dielectric and ferroelectric properties of Bi0. 5(Na0. 81, K0. 19)0. 5TiO3 ceramics were investigated. The samples were synthesized by solid state reaction technique, where powders were calcined at 850 °C for 4 h and ceramics were sintered at 1100-1150 °C for 4 h. Phase formation was determined by Xray diffraction technique (XRD). The X-ray diffraction analysis of the ceramics suggests that all samples exhibited a perovskite structure. The dielectric properties under room temperature and various temperatures were also determined. Dielectric measurement data showed that the additive influenced dielectric constant and dielectric loss. Furthermore, the hysteresis loop behaviors slightly changed with increasing the nanoparticles contents. © (2014) Trans Tech Publications, Switzerland.